2010
DOI: 10.1007/s11433-010-0193-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substrate temperature on growth of a-Si:H films by reactive facing target sputtering deposition

Abstract: Hydrogenated amorphous silicon (a-Si:H) films were deposited by reactive facing target sputtering (FTS) technique with a mixture of Ar and H 2 reaction gas. Fourier transform infrared (FTIR) absorption, Raman scattering and ultraviolet-visible optical absorption are used to investigate the microstructure and optical properties of the deposited films. The decrease of the concentration of bonded hydrogen, especially that of (Si-H 2 ) n with increasing substrate temperature (Ts), was observed in FTIR spectra, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
0
1
1
Order By: Relevance
“…2 (c) that the systematical changes in stretching vibration intensity do not occur as a function of T s , which differs from the results reported by other groups [15]. However, the microstructural factor R in our experiment, as shown in Table 3 and that of void or disordered domains, because the hydrogen atoms located in these region is in the configuration of (SiH 2 ) n (or SiH 2 ) or (SiH) n .…”
Section: Ftir Spectrumcontrasting
confidence: 89%
“…2 (c) that the systematical changes in stretching vibration intensity do not occur as a function of T s , which differs from the results reported by other groups [15]. However, the microstructural factor R in our experiment, as shown in Table 3 and that of void or disordered domains, because the hydrogen atoms located in these region is in the configuration of (SiH 2 ) n (or SiH 2 ) or (SiH) n .…”
Section: Ftir Spectrumcontrasting
confidence: 89%
“…24) FTS has already been used for the low-damage and high-rate deposition of TCO, metal, metal oxide, and magnetic materials. [25][26][27][28][29] Although the deposition of a-Si:H by FTS was reported by Wei et al, 30) the passivation quality of a-Si:H deposited by FTS on c-Si has not been reported yet. In this study, we investigated the effect of RF power on the c-Si surface passivation quality of i-a-Si:H deposited by FTS.…”
mentioning
confidence: 99%